1980
DOI: 10.1071/ar9800943
|View full text |Cite
|
Sign up to set email alerts
|

Transport and distribution of manganese in two cultivars of soybean (Glycine max (L.) Merr.)

Abstract: Transport and distribution patterns of manganese were studied in soybeans (cultivars Lee and Bragg) grown over a wide range of manganese supply levels in solution culture. Increasing the manganese supply from 1.8 �M to 450 .�M produced symptoms of manganese toxicity and reduced growth in both cultivars. Symptoms and dry matter yield reductions were more severe in Bragg. Manganese taken up by the plant was preferentially transported to young expanding tissue, while the amount moving to older tissue, including c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…As reported for many other crop plants, the middle and lower leaves acted as a sink for the accumulation of Mn (Heenan and Campbell, 1980;Tinker, 1981). Upper and middle leaves in plants at 0.61 mM Mn tolerated levels of up to 3000#gg -j Mn in their tissue before any toxicity symptoms were evident.…”
Section: Changes In the Growth And Form Of Potato Plants With Mn Stressmentioning
confidence: 98%
“…As reported for many other crop plants, the middle and lower leaves acted as a sink for the accumulation of Mn (Heenan and Campbell, 1980;Tinker, 1981). Upper and middle leaves in plants at 0.61 mM Mn tolerated levels of up to 3000#gg -j Mn in their tissue before any toxicity symptoms were evident.…”
Section: Changes In the Growth And Form Of Potato Plants With Mn Stressmentioning
confidence: 98%
“…In general, a high degree of oxidation of Fe compounds, Fe precipitation on carbonates and/or phosphates, and competition of trace metal cations with Fe 2+ for the same binding sites of chelating compounds are responsible for a low Fe uptake within plants (Kabata-Pendias, 2010). Heenan and Campbell (1980) reported that the leaves accumulated higher Mn concentrations than in phloem root exudates, fruits and seeds. The Zn distribution in plant parts usually follows the pattern: roots > foliage > branch > trunk.…”
Section: Characteristics Of Cultivated Soilsmentioning
confidence: 99%
“…Ο ίδιος συγγραφέας υποστηρίζει ότι το Μn συνήθως μετακινείται στους μεριστωματικούς ιστούς, και παρατήρησε ότι ως επί το πλείστον η συγκέντρωσή του αυξάνεται στους νέους αυξανόμενους ιστούς. Ωστόσο, οι Heenan and Campbell (1980) αναφέραν ότι, όταν υπήρχαν υψηλές συγκεντρώσεις μαγγανίου στο έδαφος, τα φύλλα συσσώρευαν υψηλότερες συγκεντρώσεις με την αύξηση της ηλικίας, αλλά μόνο μικρές ποσότητες μετατοπίζονταν από τα ώριμα φύλλα στα νεαρά, όταν υπήρχε ανεπάρκεια του στοιχείου στο έδαφος. Έτσι, το Mn φάνηκε να έχει χαμηλή κινητικότητα, όταν η πρόσληψη από το έδαφος ήταν περιορισμένη.…”
Section: επίδραση του φαινολογικού σταδίου στη μετακίνηση των ανόργανων στοιχείων στα εσωτερικά όργανα του φυτούunclassified